Reconstruction of nasal ala and tip following skin cancer resection - Park, Young Ji; Kwon, Gyu Hyeon; Kim, Jun Oh; Ryu, Woo Sang; Lee, Kyung Suk (Archives of craniofacial surgery, 2019)
Defects of the nasal ala and tip have a complex three-dimensional structure that makes them challenging to reconstruct. Many reconstructive options have been described for nasal ala and tip defects, ranging from primary closure to local flaps and skin grafts. However, it is difficult to determine which method will yield the best cosmetic results in each individual case. Thus, the purpose of this study was to determine which surgical procedures for reconstructing defects of the nasal ala and tip have better cosmetic results. From 2008 to 2018, 111 patients underwent surgery to reconstruct skin defects after resection of skin cancer in the nasal ala or tip. Their charts were reviewed to obtain data on age, sex, surgical location, size of the defect, surgical method, and cosmetic results using a visual analog scale (VAS). For nasal ala reconstruction, the most commonly used surgical technique was the nasolabial flap (n= 42). This method also had the highest VAS score (7/10). The most commonly selected surgical method for nasal tip reconstruction was the bilobed flap (n= 13), and bilobed flaps and primary closure had the highest VAS score (7/10). Nasolabial flaps showed excellent cosmetic results for the reconstruction of nasal ala defects, while primary closure and bilobed flaps yielded excellent cosmetic results for the reconstruction of nasal tip defects.